2005
DOI: 10.1038/nsmb991
|View full text |Cite
|
Sign up to set email alerts
|

MDC1 interacts with Rad51 and facilitates homologous recombination

Abstract: Mediator of DNA damage checkpoint protein-1 (MDC1) is a recently identified nuclear protein that participates in DNA-damage sensing and signaling. Here we report that knockdown of MDC1 by RNA interference results in cellular hypersensitivity to the DNA cross-linking agent mitomycin C and ionizing radiation and in impaired homology-mediated repair of double-strand breaks in DNA. MDC1 forms a complex with Rad51 through a direct interaction with the forkhead-associated domain of MDC1, not the BRCA1 C-terminal dom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
90
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 110 publications
(98 citation statements)
references
References 35 publications
7
90
0
1
Order By: Relevance
“…Its binding to Rad51 does not seem to require phosphorylation 19 whereas its binding to ATM occurs via a phospho-Ser motif rather than an expected phospho-Thr motif. 58 Structural analysis coupled with oriented peptide library screening experiments based on both pSer and pThr peptides should help define the binding specificity of the FHA domain of MDC1.…”
Section: Box 2-the Fha and Brct Domainsmentioning
confidence: 99%
See 3 more Smart Citations
“…Its binding to Rad51 does not seem to require phosphorylation 19 whereas its binding to ATM occurs via a phospho-Ser motif rather than an expected phospho-Thr motif. 58 Structural analysis coupled with oriented peptide library screening experiments based on both pSer and pThr peptides should help define the binding specificity of the FHA domain of MDC1.…”
Section: Box 2-the Fha and Brct Domainsmentioning
confidence: 99%
“…Therefore, the main mechanism of action of MDC1 in HR is mediated by the regulation of Rad51 stability, which affects its recruitment to DSBs and subsequent repair. 19 It was discovered that there is an interaction between the FHA domain of MDC1 and Rad51. 19 The interaction between MDC1 and Rad51 is direct and constitutive, as it is not influenced by IR.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…To determine how CTCF functions in the HR, we analyzed X-ray irradiation-induced Rad51 foci formation in the CTCF knockdown cells, since Rad51 is a key repair factor in HR (32)(33)(34), and aggregates into DNA repair foci after ionizing irradiation or DNA damage-inducing drug treatment (35,36). We found that the knockdown decreased the percentage of cells with five or more X-ray-induced Rad51 foci decreased from 42.13% to <10.17% (Fig.…”
Section: Ctcf Interacts With Rad51 and Is Necessary For Formation Ofmentioning
confidence: 99%